MINAT KULIAH DAN INFORMASI TENTANG UNIVERSITAS MUHAMMADIYAH SEMARANG DI KALANGAN SISWA KELAS III SEKOLAH LANJUTAN TINGKAT ATAS DI PANTURA JAWA TENGAH - Sukojo -; Setia Budhi Wilardjo (Universitas Muhammadiyah Semarang, 2006)
The existence of a significant number of private universities colleges in Central Java, particularly in Semarang has triggered a tight competition to win the prospective students. Such condition requires the management of higher education to always be agile to the changes in the environment and public demands. This research aims at describing the interest of high school’s students to go the college/universities and describing the extend of information about Muhammadiyah University of Semarang (Unimus) has reached them. Both information is very crucial and useful for the management of Unimus to determine further steps in capturing the prospective customers (students) and in meeting their needs. The research methods being deployed in this study are both quantitative and qualitative methods. The data were obtained from the questionaries. The samples were drawn through the random sampling technique comprising of the third grade students of Senior High School in the northern coast of Central Java. The statistic method being used for analyzing the data is the multiple regression analysis. The study found that 77.8% of the respondents or as many as 1.722 students have interest to study further in the university or college and 19.2% of respeondents want o work immediately after graduating from High School. Based on teh level of study from the total number of students willing to continue their study, as many as 1.171 students of 68% choose S1 program and 444 students or 25.8% choose D3 program. From the total number of students who have interests to study further, only 36.8% of respondents or 814 students have known about Unimus. Therefore Unimus still has a big task to inform most of the prospective students (63.2%) if it wants to have more students in the coming years. The most significant source of information is brochure from which 243 students (29.9%) know Unimus and the least significant is newspaper with just 4.2% respondents.